Economic and Socio-Cultural Impact on Tourism Activities in Godong Ijo - Choerunisa, Siti; Dewi, Liliana; Satritama, Muhammad Andriansyah; Putra, Reza Ardian (Graduate School, Universitas Brawijaya, 2022)
The economy is a human activity related to the production, consumption, and distribution of services and goods of social culture. Meanwhile, social culture concerns unique and distinctive characteristics related to the socio-cultural aspects of each society in a sovereign country. Tourism is an activity in which there are various supporting components and facilities in an area, so tourism is directly related to the economy and socio-culture of the area. This research was conducted to discuss the impact of tourism activities in Godong Ijo Village on the economy, society, and culture. The object under study is the Godong Ijo tourist attraction located on Jl Cinangka, Serua Village, Bojongsari District, Depok. Tourism activity in Godong Ijo affects the economy and socio-culture of the surrounding community. This study uses quantitative methods and data collection techniques such as questionnaires, observations, interviews, field research, and literature research. The results showed that tourism activities positively impact the economy, such as increasing the economy of the surrounding community, job opportunities, and increasing local government revenue. The research results show that economic variables influence tourism activities, but socio-cultural variables do not influence tourism activities. Keywords: Agro-Tourism, Economy, Godong Ijo, Socio-Culture.